2009
DOI: 10.1016/j.jog.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary deformation on the island on Pantelleria: New constraints for the recent tectonic evolution of the Sicily Channel Rift (southern Italy)

Abstract: Structural observations carried out on the volcanic island of Pantelleria show that the tectonic setting is dominated by NNE-trending normal faults and by NW-striking right-lateral strike-slip faults with normal component of motion controlled by a  N 100°E oriented extension.This mode of deformation also controls the development of the eruptive fissures, dykes and eruptive centres along NNE-SSW belts that may thus represent the surface response to crustal cracking with associated magma intrusions. Magmatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 33 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…The GPS Pantelleria-relative motions shown in Figure 5a are in good agreement with the Pleistocene deformation trends of the Sicily Channel rift (Catalano et al 2009). Deformation has faded here and is larger around the Malta escarpment.…”
Section: Implications For the Central Mediterranean Tectonicssupporting
confidence: 71%
See 1 more Smart Citation
“…The GPS Pantelleria-relative motions shown in Figure 5a are in good agreement with the Pleistocene deformation trends of the Sicily Channel rift (Catalano et al 2009). Deformation has faded here and is larger around the Malta escarpment.…”
Section: Implications For the Central Mediterranean Tectonicssupporting
confidence: 71%
“…4b). By that time, extension in the Sicily Channel troughs had rotated towards an EW-direction (Catalano et al 2009) and localized between Pantelleria and Lampedusa troughs only (Catalano et al 2009) where negligible offsets (Argnani 1990) and fissural volcanisms suggest minor extension. Volcanism, fracturing and reactivation of extensional structures have ceased in Tripolitania; however, increased volcanic activity in Jebel Al Haruj (Farahata et al 2009;Cvetković et al 2010), continuity of strain along the northernmost Tripolitania from stress analysis of break-outs (Schäfer et al 1981) and Pleistocene faulting in the Jefara plain (Giraudi 1995) suggest that the tectonic regime did not come to a complete halt.…”
Section: Implications For the Central Mediterranean Tectonicsmentioning
confidence: 99%
“…1a) whose activity would have reached the acme at approximately 5 Ma. Reactivation of the fault systems accommodated SW-NE extension in the late Quaternary (Corti et al, 2006;Catalano et al, 2009). As revealed by an available seismic database (INGV, http://emidius.mi.ingv.it/DBMI11), the above-cited structural features are a source of moderate seismicity, mostly located in the Linosa graben, with shallow events (h < 25 km) and a magnitude usually from 2 to 4 (Civile et al, 2008).…”
Section: The Study Areamentioning
confidence: 96%
“…The eastern coast of the island of Malta is characterised by the occurrence of deposits of anomalous calcareous boulders (Furlani et al, 2011;Mottershead et al, 2014;Causon Deguara, 2015). Their surface is frequently covered by biogenic encrustations, which indicate without any doubt that they were detached from the mid-or sublittoral zone.…”
mentioning
confidence: 99%
“…Different authors agree on the general statement that the Late‐Miocene to Present tectonic evolution of the Pantelleria Rift and related minor structures (like the Maltese Graben System) results from the stress field imposed by the advancing Apennine‐Sicilian‐Maghrebian Belt (Argnani, ; Dart et al, ). However, the timing and kinematic details of this evolution are still debated (Argnani, ; Ben‐Avraham et al, ; Boccaletti et al, ; Catalano et al, ; Cello, ; Dart et al, ; Finetti, ; Grasso & Reuther, ; Jongsma et al, ; Reuther & Eisbacher, ). Most kinematic models proposed so far fall in three categories that can be summarized as follows (Figure a): Some authors see the Pantelleria Rift System as a pull‐apart basin developed along a dextral wrench zone—the Medina Channel Wrench, which is the SE boundary of the rift system (Ben‐Avraham et al, ; Boccaletti et al, ; Catalano et al, ; Cello, ; Finetti, ; Jongsma et al, ; Reuther & Eisbacher, ). Alternatively, Grasso and Reuther () suggested that the Pantelleria Rift System might be a pull‐apart structure associated with the NNE‐SSW Scicli wrench zone.…”
Section: Introductionmentioning
confidence: 99%